Analisis Strategi Pemasaran Tanaman Hias Anggrek di Tangerang Selatan: Peluang dan Tantangan bagi Produsen Lokal - Tetty Nur Intan Rifia (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This study aims to analyze the marketing strategy of orchid ornamental plants in South Tangerang, especially in the context of opportunities and challenges faced by local producers. Conducted in December 2023, this study took objects from 10 housewives cultivating orchid ornamental plants in South Tangerang City. The method used is descriptive qualitative, by conducting in-depth interviews and observations of local producers to understand the marketing strategies they use, as well as identifying opportunities and challenges faced in marketing their products. The results showed that local producers used a variety of marketing strategies, including local exhibitions, online sales, and cooperation with local florists. However, there are several challenges faced, including limited market access, price competition with imported products, and lack of understanding of digital marketing. In-depth discussions are conducted to evaluate effective marketing strategies and overcome the challenges faced. The implications of this research highlight the importance of developing innovative and adaptive marketing strategies for local producers in the face of increasingly fierce market competition. Recommendations include improving market access through cooperation between local producers, training on digital marketing, and improving local product branding to increase competitiveness in local and international markets. Thus, this research contributes to strengthening the local orchid cultivation sector in South Tangerang.